Village of Immigrants : Latinos in an Emerging America - Gordon, Diana R. (Book collections on Project MUSE., 2015)
"Greenport, New York, a village on the North Fork of Long Island, has become an exemplar of a little-noted national trend--immigrants spreading beyond the big coastal cities, driving much of rural population growth nationally. In Village of Immigrants, Diana R. Gordon illustrates how small-town America has been revitalized by the arrival of these immigrants in Greenport, where she lives. Greenport today boasts a population that is one-third Hispanic. Gordon contends that these immigrants have effectively saved the town's economy by taking low-skill jobs, increasing the tax base, filling local schools, and patronizing local businesses. Greenport's seaside beauty still attracts summer tourists, but it is only with the support of the local Latino workforce that elegant restaurants and bed-and-breakfasts are able to serve these visitors. For Gordon the picture is complex, because the wave of immigrants also presents the town with challenges to its services and institutions. Gordon's portraits of local immigrants capture the positive and the negative, with a cast of characters ranging from a Guatemalan mother of three, including one child who is profoundly disabled, to a Colombian house painter with a successful business who cannot become licensed because he remains undocumented. Village of Immigrants weaves together these people's stories, fears, and dreams to reveal an environment plagued by threats of deportation, debts owed to coyotes, low wages, and the other bleak realities that shape the immigrant experience--even in the charming seaport town of Greenport. A timely contribution to the national dialogue on immigration, Gordon's book shows the pivotal role the American small town plays in the ongoing American immigrant story--as well as how this booming population is shaping and reviving rural communities"--